2015
DOI: 10.1111/hdi.12340
|View full text |Cite
|
Sign up to set email alerts
|

“You know your own fistula, it becomes a part of you”—Patient perspectives on vascular access: A semistructured interview study

Abstract: The success of hemodialysis depends on functional vascular access but such an invasive, semipermanent intervention can be confronting for patients. Vascular access complications are potentially life threatening and reduce treatment satisfaction and quality of life. This study aims to describe patient perspectives on vascular access. Face-to-face, semistructured interviews were conducted with 26 adult patients receiving hemodialysis with any form of vascular access at two dialysis units in Australia. The transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 27 publications
2
54
0
Order By: Relevance
“…4 The high level of needle fear observed in our study may be clinically significant, and highlights that needle fear may have implications on treatment adherence and the choice of treatment modality. 5 Although not reaching statistical significance in this survey, the finding that needle fear was higher in PD patients, may reflect needle-avoidance as part of the decision making process regarding the choice of renal replacement therapy; however, this requires further investigation. The scarcity of published interventions to decrease needle fear in dialysis patients is remarkable given the enormous number of access cannulations, vaccinations and erythropoietin stimulating agents that dialysis patients receive.…”
Section: Needle Fear: a Point Prevalence Survey Of Dialysis Patientsmentioning
confidence: 67%
See 1 more Smart Citation
“…4 The high level of needle fear observed in our study may be clinically significant, and highlights that needle fear may have implications on treatment adherence and the choice of treatment modality. 5 Although not reaching statistical significance in this survey, the finding that needle fear was higher in PD patients, may reflect needle-avoidance as part of the decision making process regarding the choice of renal replacement therapy; however, this requires further investigation. The scarcity of published interventions to decrease needle fear in dialysis patients is remarkable given the enormous number of access cannulations, vaccinations and erythropoietin stimulating agents that dialysis patients receive.…”
Section: Needle Fear: a Point Prevalence Survey Of Dialysis Patientsmentioning
confidence: 67%
“…Our finding of needle fear in 36% of the cohort compares to a smaller Dutch study that observed 44% of 45 patients reported needle fear . The high level of needle fear observed in our study may be clinically significant, and highlights that needle fear may have implications on treatment adherence and the choice of treatment modality . Although not reaching statistical significance in this survey, the finding that needle fear was higher in PD patients, may reflect needle‐avoidance as part of the decision making process regarding the choice of renal replacement therapy; however, this requires further investigation.…”
mentioning
confidence: 99%
“…() and Taylor et al . () reported that some patients started self‐cannulating because they felt they knew their fistula better than nurses. For many of these patients, taking control had the physical benefit of hurting less.…”
Section: Discussionmentioning
confidence: 99%
“…In Taylor et al . (), self‐cannulation was also linked with building confidence and occurred when participants had successful experiences with cannulation. Moral support was also found to be critical to the maintenance of confidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation